Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have following integral and it should be simple, however whatever substitution I use and no matter how many times I integrate it by parts (or combine both) I never get the correct solution (or any alternative solution):

$$\int \frac{dx}{(x^2 + a^2)^2}$$

I'm looking for what is on the Wolfram|Alpha in the alternative solutions section: $$\frac{\arctan(\frac{x}{a})}{2a^3} + \frac{x}{2a^2(a^2 + x^2)} $$

share|cite|improve this question
Use $u = a arctan(x)$ =) – N3buchadnezzar Mar 12 '12 at 13:37
Please write down the (quite reduced) content of the two images, in the question itself. – Did Mar 12 '12 at 13:38
@DidierPiau you mean something like this? integral((dx)/((x^2 + a^2)^2)) – Dave Mar 12 '12 at 13:46
Certainly not. See here. – Did Mar 12 '12 at 13:52… – pedja Mar 12 '12 at 14:01
up vote 3 down vote accepted

$$\int\dfrac{1}{(x^2+a^2)^2}dx$$ Hint : Does there exist a function which when differentiated gives something similar to $1\over (x^2+1)$ ?

Put $\tan^{-1} \frac{x}{a} = t$. This gives $\dfrac{1}{1+(\dfrac{x}{a})^2}.\dfrac{1}{a}.dx = dt = \dfrac{a}{a^2+{x}^2}.dx$

$$\int\dfrac{1}{(x^2+a^2)^2}dx=\int \dfrac{1}{a.( (a\tan t)^2+a^2)}dt=\int \dfrac{1}{a.( a^2\tan^2 t+a^2)}dt=\int \dfrac{1}{a^3(\tan^2 t+1)}dt=\dfrac{1}{a^3}\int \cos^2 t$$

which will lead to the answer.

share|cite|improve this answer

Substitute $$x=a \hspace{3pt} \tan \theta$$

$$ dx = a\hspace{3pt} \sec^2 \theta \hspace{3pt} d\theta$$

The integral

$$ \begin{align*} \int \frac{1}{(x^2+a^2)^2} \hspace{3pt}dx &= \int \frac{\hspace{3pt}a \hspace{3pt}\sec^2 \theta }{a^4 \hspace{3pt} \sec^4 \theta}\hspace{3pt} d\theta\\ &= \frac{1}{a^3} \int \frac{1}{\sec^2 \theta}\hspace{3pt} d\theta\\ &= \frac{1}{a^3} \int \cos^2 \theta\hspace{3pt} d\theta\\ &= \frac{1}{2a^3} \int 2\hspace{3pt}\cos^2 \theta\hspace{3pt} d\theta\\ &= \frac{1}{2a^3} \int (1+\cos2 \theta)\hspace{3pt} d\theta\\ &= \frac{1}{2a^3} \theta + \frac{1}{2a^3} \frac{\sin 2\theta}{2} + \text{constant} \\ &= \frac{1}{2a^3} \tan^{-1}\frac{x}{a} + \frac{1}{2a^3} \frac{\sin 2\theta}{2} + \text{constant} \\ \tag{A}\\ \end{align*} $$

But since we substituted $x=a \hspace{3pt} \tan \theta$, which is equivalent to

$$\sin \theta = \frac{x}{\sqrt{x^2+a^2}}$$ and $$\cos \theta = \frac{a}{\sqrt{x^2+a^2}}$$

$$ \sin2\theta = 2 \sin\theta \cos\theta = \frac{2xa}{x^2+a^2}$$

The integral therefore simplifies to

$$\frac{1}{2a^3} \tan^{-1}\frac{x}{a} + \frac{1}{2a^3} \frac{ax}{x^2+a^2} + \text{constant}$$

share|cite|improve this answer

After a linear substitution we may instead look at $$\frac{1}{(1+x^2)^2}= \frac{(1+x^2)}{(1+x^2)^2}-\frac{x^2}{(1+x^2)^2}=\frac{1}{1+x^2}-\frac{x^2}{(1+x^2)^2}$$ where the first term is easy. For the second term we may try integration by parts $$\int x\cdot\frac{x}{(1+x^2)^2}dx=\left[x\cdot\frac{-1}{2(1+x^2)}\right]+\frac{1}{2}\int\frac{1}{1+x^2}dx=-\frac{x}{2(1+x^2)}+\frac12\arctan x$$ Ending up with $$\int\frac{dx}{(1+x^2)^2} = \frac12\arctan x +\frac{x}{2(1+x^2)}$$

share|cite|improve this answer

We will use integration by parts. Assume that $a$ is positive. We first make the preliminary substitution $x=at$. Then $dx=a\,dt$, and when we go through the substitution process, we end up with $\int \frac{1}{a^3}\frac{dt}{(1+t^2)^2}$.

Let's not bother to carry the constant $\frac{1}{a^3}$ around, it can be inserted at the end. So we go after $\int \frac{dt}{(1+t^2)^2}$.

We use a little trick that has a number of uses. Let $I=\int \frac{dt}{1+t^2}$. (This is not a typo!) We recognize this integral instantly, since we know that the derivative of $\arctan t$ is $\frac{1}{1+t^2}$. But let's begin to evaluate the integral by using integration by parts.

Let $u=\frac{1}{1+t^2}$ and $dv=dt$. Then $du= -\frac{2t}{(1+t^2)^2}$ and we can take $v=t$. Thus $$I=\int \frac{dt}{1+t^2}=\frac{t}{1+t^2}- \int-\frac{2t^2\,dt}{(1+t^2)^2}.$$ Get rid of the doubled minus signs, and rewrite $2t^2$ as $2+2t^2 -2$. We end up with $$I=\frac{t}{1+t^2} +\int \frac{2(1+t^2)}{(1+t^2)^2}-\int \frac{2\,dt}{(1+t^2)^2},$$ and therefore $$I=\frac{t}{1+t^2}+2I-2\int\frac{dt}{(1+t^2)^2}.$$ Thus $$2\int\frac{dt}{(1+t^2)^2}=\frac{t}{1+t^2}+I=\frac{t}{1+t^2}+\arctan t.$$ So to find $\int \frac{dt}{(1+t^2)^2}$, divide the right-hand side by $2$. And don't forget to add the arbitrary constant $C$ of integration at the end.

share|cite|improve this answer

When you see $a^2 + x^2$, think of $1+\tan^2\theta=\sec^2\theta$, and write $x=a\tan\theta$.

When you see $a^2 - x^2$, think of $1-\sin^2\theta=\cos^2\theta$, and write $x=a\sin\theta$.

When you see $x^2 - a^2$, think of $\sec^2\theta -1=\tan^2\theta$, and write $x=a\sec\theta$.

share|cite|improve this answer

Just to expand further the idea behind AD.'s answer.

Let $n\in \mathbb{N}$, $n\geq 2$ and: $$I_n(a) = \int \frac{1}{(a^2+x^2)^n}\ \text{d} x\; ,$$ where $a>0$. Multiplying and dividing by $a^2$ the RH side and adding and subtracting $x^2$ in the integrand's numerator, you get: $$\tag{1} \begin{split} I_n(a) &= \frac{1}{a^2} \int \frac{1}{(a^2+x^2)^{n-1}}\ \text{d} x - \frac{1}{a^2}\int \frac{x^2}{(a^2+x^2)^n}\ \text{d} x\\ &= \frac{1}{a^2}\ I_{n-1}(a) -\frac{1}{a^2}\int x\ \frac{x}{(a^2+x^2)^n}\ \text{d} x\; ; \end{split}$$ the integral in the rightmost side of (1) can be evaluated by parts: $$\tag{2} \begin{split} \int x\ \frac{x}{(a^2+x^2)^n}\ \text{d} x &= -\frac{1}{2(n-1)}\ \frac{x}{(a^2+x^2)^{n-1}} + \frac{1}{2(n-1)} \int \frac{1}{(a^2+x^2)^{n-1}}\\ &= -\frac{1}{2(n-1)}\ \frac{x}{(a^2+x^2)^{n-1}} + \frac{1}{2(n-1)}\ I_{n-1}(a) \end{split}$$ therefore, plugging the righmost side of (2) into (1) you get the nice recursion formula: $$\tag{3} I_n(a) = \frac{2n-3}{a^2(2n-2)}\ I_{n-1}(a) + \frac{1}{a^2(2n-2)}\ \frac{x}{(a^2+x^2)^{n-1}}\; .$$ Using (3) recursively you get: $$ \begin{split} I_n(a) &= \frac{(2n-3)(2n-5)}{a^4 (2n-2)(2n-4)}\ I_{n-2}(a) + \frac{(2n-3)}{a^4(2n-2)(2n-4)}\ \frac{x}{(a^2+x^2)^{n-2}}\\ &\phantom{=} + \frac{1}{a^2(2n-2)}\ \frac{x}{(a^2+x^2)^{n-1}}\\ &= \frac{(2n-3)(2n-5)(2n-7)}{a^6 (2n-2)(2n-4)(2n-6)}\ I_{n-3}(a) + \frac{(2n-3)(2n-5)}{a^6 (2n-2)(2n-4)(2n-6)}\ \frac{x}{(a^2+x^2)^{n-3}}\\ &\phantom{=} + \frac{(2n-3)}{a^4(2n-2)(2n-4)}\ \frac{x}{(a^2+x^2)^{n-2}} + \frac{1}{a^2(2n-2)}\ \frac{x}{(a^2+x^2)^{n-1}}\\ &=\cdots\\ &= \frac{(2n-3)!!}{a^{2n-2} (2n-2)!!}\ I_1(a)+x\ \sum_{k=1}^{n-1} \frac{1}{a^{2(n-k)}}\ \frac{(2n-3)!!}{(2k-1)!!}\ \frac{(2k-2)!!}{(2n-2)!!}\ \frac{1}{(a^2+x^2)^k}\; . \end{split}$$ Since: $$I_1(a) = \int \frac{1}{a^2+x^2}\ \text{d} x = \frac{1}{a}\ \arctan \left( \frac{x}{a}\right)$$ finally you obtain: $$ \tag{4} \begin{split} I_n(a) &= \frac{(2n-3)!!}{a^{2n-1} (2n-2)!!}\ \arctan \left( \frac{x}{a}\right) \\ &\phantom{=} +x\ \sum_{k=1}^{n-1} \frac{1}{a^{2(n-k)}}\ \frac{(2n-3)!!}{(2k-1)!!}\ \frac{(2k-2)!!}{(2n-2)!!}\ \frac{1}{(a^2+x^2)^k} \end{split}$$ which is the elementary closed form of $I_n(a)$.

If you set $n=2$ in (4) you obtain exactly: $$I_2(a) = \frac{1}{2a^3}\ \arctan \left( \frac{x}{a}\right) + \frac{x}{2a^2 (a^2+x^2)}$$ which is the correct value of your integral.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.